2007
DOI: 10.1182/blood-2007-02-071589
|View full text |Cite
|
Sign up to set email alerts
|

The May-Hegglin anomaly gene MYH9 is a negative regulator of platelet biogenesis modulated by the Rho-ROCK pathway

Abstract: IntroductionMYH9 encodes myosin-IIA, a nonmuscle myosin heavy chain that assembles within actomyosin complexes and facilitates shape changes in diverse cell types. [1][2][3] Patients with autosomal dominant inherited MYH9-related disorders, 4-6 including the May-Hegglin anomaly, 7,8 exhibit macrothrombocytopenia and variable degrees of hearing loss, nephritis, and cataracts. These individuals experience mild bleeding symptoms as a result of reduced numbers of misshapen blood platelets that can be 2 to 5 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
165
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 150 publications
(178 citation statements)
references
References 50 publications
12
165
0
1
Order By: Relevance
“…S3E) (25). The morphology effects are reminiscent of blebbistatin, causing an increased number of MKs with proplatelet extensions when cells are grown on plastic (13,14), and we indeed find an approximately threefold increase in mean length of proplatelet extensions under such conditions (Fig. 2E).…”
Section: Results and Analysissupporting
confidence: 52%
See 2 more Smart Citations
“…S3E) (25). The morphology effects are reminiscent of blebbistatin, causing an increased number of MKs with proplatelet extensions when cells are grown on plastic (13,14), and we indeed find an approximately threefold increase in mean length of proplatelet extensions under such conditions (Fig. 2E).…”
Section: Results and Analysissupporting
confidence: 52%
“…In mouse, deletion of MYH9 in MKs also produces MayHegglin-like defects (12,13). Paradoxically, pharmacological inhibition of NMM-II ATPase by blebbistatin in mouse adult (13) and mouse embryonic (14) systems is reported to produce a two-to ∼threefold increase in proplatelet extensions but not affect MK ploidy or size, at least for the doses or times tested. Whether human MK-poiesis is regulated by myosin-II has remained unclear, but possible pathways include direct phosphorylation of NMM-II (i.e., heavy-chain regulation that decreases myosin activity in other cells) (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Recent findings have shown that NMMHC-IIA attenuates proplatelet formation, 33,34 which occurs in terminally mature megakaryocytes where most of the cytoplasm is converted into lengthy beaded extensions. 35 Thus, NMMHC-IIA might restrain thrombopoiesis until megakaryocytes accumulate sufficient quantities of the materials required for optimal platelet assembly; loss of myosin-IIA function could trigger precocious proplatelet formation, whereas gain-of-function mutations might limit platelet production.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not a dominant negative effect of mutant allele or haploinsufficiency is responsible for hematological abnormalities [23][24][25] is still controversial. The role of NMMHC-IIA in megakaryocyte differentiation and platelets release also needs to be investigated [26]. …”
Section: Related Disorders and Unsolved Issuesmentioning
confidence: 99%